A facile sonochemical protocol for synthesis of 3-amino- and 4-amino-1,2,4-triazole derived Schiff bases as potential antibacterial agents - Sultan, Aeysha; Ur Rehman, Mian Habib; Sajjad, Noreen; Irfan, Ali; Ullah, Irfan; Mustaqeem, Muhammad; Saleem, Muhammad; Rubab, Syeda Laila; Rafiq, Muhammad; Khalid, Muhammad; Kotwica-Mojzych, Katarzyna; Mojzych, Mariusz (PLOS ONE, 2020)
A facile method has been developed for the synthesis of Schiff bases derived from substituted and unsubstituted 3-amino- and 4-amino-1,2,4-triazoles. Condensation of the aminotrizoles with a variety of aromatic aldehydes afforded desired Schiff bases in excellent yields in 3–5 minutes of exposure to ultra-sound. The synthesized compounds were characterized by means of IR, 1HNMR and Mass spectrometry. The synthesized compounds were also screened for their antibacterial potential against Gram-negative (Escherichia coli, Shigella sonnei, Pseudomonas aeruginosa and Salmonella typhi) and two Gram-positive (Staphylococcus aureus and Bacillus subtilis) strains.